2011
DOI: 10.1128/mcb.01389-10
|View full text |Cite
|
Sign up to set email alerts
|

MICAL-1 Is a Negative Regulator of MST-NDR Kinase Signaling and Apoptosis

Abstract: Article abstract-Objective: To present the clinical, neuroimaging, and electrophysiologic characteristics of a variant AD phenotype. Background: The authors have identified a large Finnish kindred with presenile dementia and spastic paraparesis due to deletion of exon 9 of presenilin 1. Neuropathologic analysis showed unusual cortical "cotton wool" plaques, immunoreactive for the beta-amyloid peptide but lacking congophilic cores. Patients and Methods: Twenty-two affected individuals (16 men and 6 women) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 76 publications
2
68
0
Order By: Relevance
“…Oxidative stress originates from an imbalance between the generation and scavenging of ROS, activates aberrant signalling cascades and leads to tumorigenesis. A recent study reported that increased ROS production was triggered by overexpression of constitutively active MICAL1 mutants 16. On the contrary, ROS levels were significantly attenuated upon transfection of the enzymatically impaired FAD domain mutant 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress originates from an imbalance between the generation and scavenging of ROS, activates aberrant signalling cascades and leads to tumorigenesis. A recent study reported that increased ROS production was triggered by overexpression of constitutively active MICAL1 mutants 16. On the contrary, ROS levels were significantly attenuated upon transfection of the enzymatically impaired FAD domain mutant 4.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the anti‐apoptosis effect of MICAL1 in human melanoma cells. The mechanism was demonstrated to be associated with MICAL1's negative control of mammalian Ste‐20‐like kinase 1 (MST1)‐nuclear‐Dbf2‐related kinase (NDR) apoptotic signalling by competing with MST1 for NDR binding 5, 16. Despite its characteristic on anti‐apoptosis, whether MICAL1 could influence cancer cell proliferation and the underlying molecular mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…NDR1 belongs to the NDR/LATS subgroup of the AGC serine/threonine kinase family [33,34] and is activated by Fas, TNF-α, osmotic and oxidative stresses [35][36][37]. Therefore, our Y2H results suggested that NDR1 might function together with RalA and MAP4K4 upstream of p38 activation in the osmotic stress response.…”
Section: Rala Map4k4 and Ndr1 Mediate Stress-activated P38 Kinase Phmentioning
confidence: 76%
“…More specifically, our study expands our understanding of how RalA signaling pathways mediate SAPK activation and determines the role of RalA in apoptosis induced responses to different types of environmental stresses. We identified MAP4K4 as a new upstream kinase of NDR1 (also known as STK38), an AGC serine/threonine protein kinase [33,34] that can be activated by Fas, TNF-α, osmotic and oxidative stresses [35][36][37]. Moreover, we demonstrate that RalA regulates NDR1 activation, via Exocyst and MAP4K4 signaling, to trigger apoptosis in response of extracellular stresses.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation